Analisis User Experience Quizizz pada Gamification di Bidang Pendidikan Menggunakan Metode User Experience Questionnaire (UEQ) - Siregar, Muslim Putra Perdana; Saputra, Eki; Fronita, Mona; Marsal, Arif; Muttakin, Fitriani (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Quizizz exists as technology develops. However, in using Quizizz there are still many users who experience and give negative responses to their experience in using it. The reason the UEQ method is used in this research is because the UEQ method provides speed in processing and provides special tools that have been provided on the official UEQ website. In this study using the UEQ method, the resulting evaluation value of several variables is positive and neutral, including 5 variables with positive results. Among them are the variables of Attractiveness (mean 1.133), Clarity (mean 1.018), Efficiency (mean 1.198), Appropriateness (mean 1.130), and Stimulation (mean 1.170). While the remaining 1 variable received a Neutral evaluation, namely Novelty (mean 0.595). From some of the mean evaluation results obtained, the authors conclude that the Quizizz application received a positive evaluation by users in their experience while using the Quizizz application. Recommendations obtained in this research in the form of the appearance of the Quizizz application must be more user friendly and also in terms of information must be constantly updated using short, concise, and clear language so that it can be easily understood by students in educational institutions in SMA 6 Negeri Padangsidimpuan.